2015
DOI: 10.4038/tar.v25i2.8137
|View full text |Cite
|
Sign up to set email alerts
|

Preference for different intensities of red light as affected by the age, temporal variation and behaviour of broiler birds

Abstract: The red light (RD) marks high preference (PR), weight gain and welfare of broilers. A study was conducted to determine the PR for high (HI; 320 lux), medium (MI; 20 lux), dim (DI; 5 lux) intensities of RD and to investigate whether such PRs are influenced by age (AG), temporal variation (TV) and behaviour. The PR-chambers consisting of three identical compartments were provided with ad libitum feed, water and illumination from 5W incandescent bulbs (20 lux, 20 L:4D). A randomized complete block design was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
(13 reference statements)
1
3
0
Order By: Relevance
“…These results agreed with the report of Mohamed et al (2017) who reported beneficial impact on growth performance of broilers reared under three monochromatic led lights (white, green and blue). This finding is also in line with Senaratna et al (2008) who reported that broilers reared under red colour light showed a tendency to gain higher body weight compared to those reared under white light. Birds in blue, red and green light and troughs had positive effect on total body weight and these are in agreement with the report of Olanrewaju et al (2006).…”
Section: Behaviour Of Birds Fed Under Different Colour Of Lights and ...supporting
confidence: 92%
“…These results agreed with the report of Mohamed et al (2017) who reported beneficial impact on growth performance of broilers reared under three monochromatic led lights (white, green and blue). This finding is also in line with Senaratna et al (2008) who reported that broilers reared under red colour light showed a tendency to gain higher body weight compared to those reared under white light. Birds in blue, red and green light and troughs had positive effect on total body weight and these are in agreement with the report of Olanrewaju et al (2006).…”
Section: Behaviour Of Birds Fed Under Different Colour Of Lights and ...supporting
confidence: 92%
“…This temperature was gradually reduced by 2 °C to 3 °C weekly until the final temperature of 25 °C was reached, https://doi.org/10.17221/178/2022-CJAS time (1 h); the average time (s) refers to the average duration of certain behaviour per unit time (1 h), and the maximum time and minimum time (s) indicate that certain behaviour could continue to occur in a unit of time (1 h). The behavioural category and description of broilers were in accordance with those mentioned in Riber et al (2017) and Senaratna et al (2015) (Table 2).…”
Section: Experimental Design Animals and Dietsmentioning
confidence: 82%
“…When exposed to red or red-yellow lights, broilers become more agitated and fearful, whereas blue or green-blue lights lowered their activity . On the other hand, in the case of the Hybro broiler chicken, the weight of the chicken body, feed intake (FI), water consumption patterns, and feed conversion ratio were not significantly affected by red and white color during nighttime (Senaratna, et al, 2008). Meanwhile, a metaanalysis study by Lewis and Morris (2000) found that the growth rate of broiler chickens under white light and red color light exposure was the same and suggested using longer wavelengths for suppressing growth rather than promoting growth with shorter wavelengths.…”
Section: Performance During the Rearing Periodmentioning
confidence: 97%